Synthesis of reconfigurable information security hardware on HPC platforms - Евдокимов, Виктор Федорович; Давиденко, Анатолий Николаевич; Гильгурт, Сергей Яковлевич (Ukrainian Information Security Research Journal, 2018)
The main purpose of a signature-based network intrusion detection system (NIDS) is to inspect network packet contents against tens of thousands of predefined malicious patterns. Unlike the firewall, NIDS examines not only packet headers, but also the packet bodies. The multi-pattern string matching task is a specific type of string matching functionality to search an input stream for a set of patterns rather than a single pattern. Due to rising traffic rates, increasing number and sophistication of attacks and the collapse of Moore’s law for sequential processing, traditional software solutions can no longer meet the high requirements of today’s security challenges. Therefore, hardware approaches are proposed to accelerate pattern matching. Combining the flexibility of software and the nearASIC performance, reconfigurable FPGA-based devices have become increasingly popular for this purpose. Unfortunately, the development of complex reconfigurable devices is a very difficult craft. Users of NIDS which are usually system administrators have not neither enough qualification, nor computing resources to fulfill such a work. On the other hand specificities of security tasks require frequent execution of dynamic re-synthesis of reconfigurable accelerators. To solve this problem, a centralized system based on GRID and Cloud platforms was proposed. Such approach moves design and computation complexities from LANs to HPC. An experimental system was constructed and tested. First results are received and discussed. Preliminary comparison of GRID and Cloud technologies is made. Besides cybersecurity, high-speed multi-pattern matching is required for such important applications as data mining, XML switching, QoS management, VoIP filtering, cache replication etc.